2023
DOI: 10.1371/journal.pone.0280241
|View full text |Cite
|
Sign up to set email alerts
|

The experience of noise in communication-intense workplaces: A qualitative study

Abstract: Objective The aim of the study was to explore and describe how workers in communication-intense workplaces in health care and preschools experience the sound environment. The dependence on vocal communication and social interaction poses a challenge using hearing protection in these working environments. Method A qualitative method was used, more specifically inductive thematic analysis was used, as this approach was deemed suitable to explore the staff’s experiences of the sound environment. Data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Informants discussed this issue in a qualitative study where employees in communication-intense workplaces such as health care and preschools were asked how they experienced their sound environment. The authors found that the informants considered workplace noise meaningful but disturbing [60]. Preschool teachers explained that they "needed to be constantly attentive to sounds, in order to be aware of what was going on among the children" [60, p.6].…”
Section: Factor 5 Hearing Loss-related Symptomsmentioning
confidence: 99%
“…Informants discussed this issue in a qualitative study where employees in communication-intense workplaces such as health care and preschools were asked how they experienced their sound environment. The authors found that the informants considered workplace noise meaningful but disturbing [60]. Preschool teachers explained that they "needed to be constantly attentive to sounds, in order to be aware of what was going on among the children" [60, p.6].…”
Section: Factor 5 Hearing Loss-related Symptomsmentioning
confidence: 99%
“…Occupational fatigue caused by noise occurs through mechanisms of psychological and physical disturbances in workers (Radun et al, 2022). Noise can disrupt concentration, interfere with communication, and create stress (Fitria & Malik, 2022), all of which can contribute to occupational fatigue (Gyllensten et al, 2023). When workers work in a very noisy environment, the body will increase the body's metabolism process, thus requiring energy from lactate acid (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%